Effect of Low-Temperature Storage on Chemical Composition and Antimicrobial Activity of Honey - Dmitry V. Gruznov; Olga A. Gruznova; Alexey B. Sokhlikov; Anton V. Lobanov (Техника и технология пищевых производств)
Natural honey can change its physicochemical and biological properties during storage. According to State Standard 19792-2017, honey should be stored at ≤ 20°C. Some publications promote long-term storage of honey at temperatures between 0 and –20°C that preserves its physicochemical parameters, especially the content of hydroxymethylfurfural. Promising as they seem, such temperature modes may affect other physicochemical parameters of honey. The research objective was to study the effect of different temperature conditions on various honey samples and their physicochemical and biological parameters during long-term storage. The study applied standard and authentic research methods to fresh linden, buckwheat, and sunflower honey samples obtained from Rostov, Volgograd, Kursk, Voronezh, Saratov, and Krasnodar regions. They were stored in heat, cold, and moisture test chambers M-60/100-500 for 12 months. Hydroxymethylfurfural proved stable at –18°C for 12 months. After 12 months at 18°C, it showed a sharp increase of 472.5–488.1%. The activity of enzymic diastase, D-glucose-1-oxidase, and catalase occurred at all temperature modes after 1 month of storage. At 0–5°C, the changes were minimal: hydrogen peroxide (H2O2) remained stable, and its concentration decreased by ≤ 12.2% after 12 months of storage. Moisture, mass fraction of reducing sugars, and acidity remained stable in all samples. An antimicrobial test by Escherichia coli (strain 1257), Staphylococcus aureus (strain 209-P), and Bacillus cereus (strain 96) showed that the best inhibiting properties belonged to the samples of linden and buckwheat honey stored at 5 and 0°C for 12 months. The optimal temperatures for long-term honey storage were in the range between 5 and 0°C. The results obtained can be used in updated honey storage standards.